2015
DOI: 10.1074/jbc.m115.648428
|View full text |Cite
|
Sign up to set email alerts
|

The Tyrosine Kinase c-Src Specifically Binds to the Active Integrin αIIbβ3 to Initiate Outside-in Signaling in Platelets

Abstract: Background: ␤3-bound c-Src initiates outside-in signaling in platelets. Results: After platelet stimulation, ␤3 binds to the c-Src SH3 domain at a site overlapping with its PPII helix binding site. Conclusion:The interaction of c-Src with ␤3 requires c-Src activation to vacate the PPII helix binding site. Significance: The mode of c-Src binding to ␤3 prevents c-Src-mediated signaling in circulating platelets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 34 publications
2
18
0
1
Order By: Relevance
“…41 In addition to this, Src family kinases (SFKs), specifically c-Src, have been shown to be crucial for integrin outside-in signaling, and quercetin potently inhibits SFKs including Fyn and Lyn. 35 42 An inhibition of platelet activation induced by thrombin here agrees with the GPCR-stimulated aggregometry presented in this study, and offers further evidence for quercetin and its metabolites as inhibitors of the thrombin-stimulated platelet activation pathway, even in the presence of plasma proteins. Quercetin has also exhibited anticoagulant activities in numerous studies, including inhibitory effects on the enzymatic activity of thrombin and Factor Xa.…”
Section: Discussionsupporting
confidence: 87%
“…41 In addition to this, Src family kinases (SFKs), specifically c-Src, have been shown to be crucial for integrin outside-in signaling, and quercetin potently inhibits SFKs including Fyn and Lyn. 35 42 An inhibition of platelet activation induced by thrombin here agrees with the GPCR-stimulated aggregometry presented in this study, and offers further evidence for quercetin and its metabolites as inhibitors of the thrombin-stimulated platelet activation pathway, even in the presence of plasma proteins. Quercetin has also exhibited anticoagulant activities in numerous studies, including inhibitory effects on the enzymatic activity of thrombin and Factor Xa.…”
Section: Discussionsupporting
confidence: 87%
“…22,55,61 More recent work demonstrates, however, that c-Src associates with b 3 predominantly after platelet activation. 62 Furthermore, an interaction of Ga 13 with an ExE motif in the b 3 -integrin tail has been demonstrated as a key early event required for the activation of c-Src to initiate outside-in signaling, a process Reduced tail-bleeding time.…”
Section: Src-family Kinasesmentioning
confidence: 99%
“…The kinase of Src family is well-known to be the downstream target of integrin, in which Src is a key member 29 . Previous study revealed that Src is able to activate Erk, a kinase that can phosphorylate p47 phox and then induce its membrane translocation 30 , 31 .…”
Section: Resultsmentioning
confidence: 99%